Exploring Public Perception of Paratransit Service Using Binomial Logistic Regression - Tri Basuki Joewono; Hisashi Kubota (Institute of Research and Community Outreach - Petra Christian University, 2007)
Knowledge of the market is a requirement for a successful provision of public transportation. This study aims to explore public perception of paratransit service, as represented by the user and non-user of paratransit. The analysis has been conducted based on the publicâs response, by creating several binomial logistic regression models using the public perception of the quality of service, quality of car, quality of driver, and fare. These models illustrate the characteristics and important variables to establish whether the public will use more paratransit in the future once improvements will have been made. Moreover, several models are developed to explore public perception in order to find out whether they agree to the replacement of paratransit with other types of transportation modes. All models are well fitting. These models are able to explain the respondentsâ characteristics and to reveal their actual perception of the operation of paratransit. This study provides a useful tool to know the market in greater depth.